Essential concepts & school-based cases in special education law - Russo, Charles J. 4 0 16; Osborne, Allan G.; 5 (Thousand Oaks, CA : Corwin Press, 2008)
A guide to understanding how the Individuals with Disabilities Education Improvement Act and its accompanying regulations apply in the classroom, discussing entitlement to special education services, procedural due process, disciplinary sanctions for students with disabilities, antidiscrimination laws, and other topics, and including excerpts from selected legal decisions.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Law and legislation;Law and legislation. -- Special education;Educators;Special education;Educators -- United States.;United States;United States;United States -- Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2